2020
DOI: 10.1021/acs.est.9b07485
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Conditions on Secondary Organic Aerosol Production from Photosensitized Humic Acid

Abstract: Recent studies have shown the potential of the photosensitizer chemistry of humic acid, as a proxy for humic-like substances in atmospheric aerosols, to contribute to secondary organic aerosol mass. The mechanism requires particle-phase humic acid to absorb solar radiation and become photoexcited, then directly or indirectly oxidize a volatile organic compound (VOC), resulting in a lower volatility product in the particle phase. We performed experiments in a photochemical chamber, with aerosol-phase humic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…As described previously in Section , photosensitized processing, involving a catalytic cycle of electronic excitation of an absorbing species to its triplet state and energy transfer to another otherwise unreactive species, has been shown to occur for particulate BrC. ,,, For surrogate photosensitizers of humic acid and 4-benzoylbenzoic acid in mixed organic and inorganic matrixes, exposure to UVA light and high concentrations of limonene, roughly 300 ppb, resulted in particle growth, likely due to the production of oxidants at the air–particle interface after excitation of humic acid, followed by reaction with colliding limonene molecules . Recently, this mechanism has been investigated for particulate BrC under a broader range of conditions.…”
Section: Particulate Phase Reactions Of Brcmentioning
confidence: 89%
See 2 more Smart Citations
“…As described previously in Section , photosensitized processing, involving a catalytic cycle of electronic excitation of an absorbing species to its triplet state and energy transfer to another otherwise unreactive species, has been shown to occur for particulate BrC. ,,, For surrogate photosensitizers of humic acid and 4-benzoylbenzoic acid in mixed organic and inorganic matrixes, exposure to UVA light and high concentrations of limonene, roughly 300 ppb, resulted in particle growth, likely due to the production of oxidants at the air–particle interface after excitation of humic acid, followed by reaction with colliding limonene molecules . Recently, this mechanism has been investigated for particulate BrC under a broader range of conditions.…”
Section: Particulate Phase Reactions Of Brcmentioning
confidence: 89%
“…[212][213][214] Irradiation can break apart chromophores, produce oxidants in situ, or facilitate photosensitized reactions. 144,164,212,215 Reactive uptake of ammonia or amines to dicarbonyl-containing organic aerosol, or conversely of dicarbonyl compounds to ammonium-containing aerosol, can lead to the formation of imine and nitrogen-containing BrC. 213,[216][217][218] Heterogeneous reactions with gaseous ozone and OH and NO3 radicals can lead to oxidative aging, resulting in changes in both composition and absorptivity.…”
Section: Cloud and Fog Droplet Evaporation Processes Leading To Brcmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, irradiation of imidazole‐2‐carboxaldehyde (IC) and humic acid in the presence of various gaseous VOCs, such as d‐limonene, has been shown to produce highly oxygenated compounds and thereby initiate aerosol growth by photosensitized mechanisms (Aregahegn et al., 2013; González Palacios et al., 2016; Monge et al., 2012; Rossignol et al., 2014; Tsui et al., 2017). Previous studies have suggested that the photosensitized chemistry of humic‐like substances (HULIS) is not fast enough to compete with the conventional free‐radical‐driven growth under ambient concentrations of d‐limonene (Fankhauser et al., 2020). However, while not being a major growth pathway of aerosols, photosensitized processes have the potential to change the particle phase oxidation capacity.…”
Section: Introductionmentioning
confidence: 99%
“…But this only allows to simulate a limited part of atmospheric photochemistry. Other similar chambers have solved this issue by using either xenon arc lamps (CESAM chamber; Wang et al, 2011) fluorescent tubes or black light ( PACS-C3: Platt et al, 2013;Fankhauser et al, 2020) or single wavelength LEDs (CLOUD-chamber: Lehtipalo et al, 2018). LEDs and fluorescent tubes have the advantages that they are easy to use, emit less heat and are relatively costefficient.…”
Section: Introductionmentioning
confidence: 99%